Pembangunan Desa dan Kesejahteraan Masyarakat Melalui Kebijakan Dana Desa: Kasus Partisipasi Masyarakat Desa di Kabupaten Luwu Timur - Rabina Yunus (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2022)
This research was conducted to identify the level of community participation in participatory activities at the research location. This research focuses on the unknown story of community participation in village development in East Luwu Regency, South Sulawesi Province, and the lack of strategies to increase community participation offered. This study aims to identify the level of community participation and formulate strategies to increase community participation in village development activities in the region. Community participation is one of the factors that influence the success of development programs and rural community development. Community participation is needed to realize village development by the needs of the village itself. Community involvement does not only involve the community in the process of making decisions about each development program but also involves the community in identifying problems and opportunities that exist in the community. Every development activity will fail if there is no community participation. In the same way, the community must be involved in the use and management of village funds so that their use and management are more targeted and beneficial to society. In Solo Village, Angkona District, East Luwu Regency, South Sulawesi Province, village funds are still poorly used and the community is not involved. This has an impact on community support for various initiatives that will be implemented with village funds.